2014
DOI: 10.1155/2014/458329
|View full text |Cite
|
Sign up to set email alerts
|

ANN-Based Estimation of Groundwater Quality Using a Wireless Water Quality Network

Abstract: Water is essential for life. Considering its importance for humans, it must be periodically analyzed to ensure its quality. In this study, a wireless water quality network is deployed to collect water quality parameters periodically and an artificial neural network-based estimation method is proposed to estimate groundwater quality. Estimating groundwater quality enables the authorities to take immediate actions for ensuring water quality. Compared to traditional water quality analysis methods, the proposed me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…Then, they applied three typical MLP architectures to complete the Tur prediction whose inputs were NH 3 -N, EC, DO, pH, and WT. Klçaslan et al [128] randomly divided the datasets and pointed out that when the data tended to be roughly periodic after a year, the time length of data acquisition, covering a long period such as a year or more was highly recommended in order to capture long-term variation. Yang et al [129] found the most significant parameters by using analysis of variance (ANOVA) techniques.…”
Section: Artificial Neural Network Models For Water Quality Predictionmentioning
confidence: 99%
“…Then, they applied three typical MLP architectures to complete the Tur prediction whose inputs were NH 3 -N, EC, DO, pH, and WT. Klçaslan et al [128] randomly divided the datasets and pointed out that when the data tended to be roughly periodic after a year, the time length of data acquisition, covering a long period such as a year or more was highly recommended in order to capture long-term variation. Yang et al [129] found the most significant parameters by using analysis of variance (ANOVA) techniques.…”
Section: Artificial Neural Network Models For Water Quality Predictionmentioning
confidence: 99%
“…This technique, due to Levenberg [30] and Marquardt [31], is a combination of the following two methods [32,33]:…”
Section: Artificial Neural Network-based Control Of a Multiboat Groupmentioning
confidence: 99%
“…The optimization method known as Levenberg-Marquardt algorithm [29] was used for the development of the proposed NN. This technique, due to Levenberg [30] and Marquardt [31], is a combination of the following two methods [32,33]:…”
Section: Artificial Neural Network-based Control Of a Multiboat Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…With the developing of wireless sensor network technology, a variety of applications based WSN appear, such as land cover classification [1], SCR node detection in vehicular network [2], fault detection [3, 4], and groundwater quality estimation [5]. Traditionally, these applications analyze sample data in a fusion center [6].…”
Section: Introductionmentioning
confidence: 99%